STRATEGI GURU DALAM MEMBENTUK KARAKTER KEDISIPLINAN DAN TANGGUNG JAWAB SISWA SEKOLAH DASAR (STUDI DI MIS ASY-SYA’BAN KARANGSARI) - Shiva Amiliya Aidah; Bagas Mukti Nasrowi (CV. Denasya Smart Publisher, 2026)
This study aims to describe the teachers’ strategies in developing students’ discipline and responsibility character at MIS Asy-Sya’ban Karangsari. This research was motivated by the existence of students who were still lacking discipline in obeying school rules, lacking responsibility toward assignments, and having low awareness of maintaining orderliness and personal neatness. Therefore, appropriate teacher strategy are needed to build students’ character through habituation activities and exemplary behavior within the school environment. This study employed a qualitative approach with a descriptive qualitative design. The data sources in this study were teachers and students at MIS Asy-Sya’ban Karangsari. Data collection techniques were conducted through semi-structured interviews and non-participant observation. Data validity was ensured through source triangulation, method triangulation, and time triangulation. Data analysis used the Miles and Huberman model, including data condensation, data collection, data display, and data verification. The results showed that teacher strategies in developing students’ discipline character were carried out through habituation, routine supervision, implementation of rules, educational sanctions, and routine school activities such as collective prayer and literacy journals. Meanwhile, the strategy for developing responsibility character was implemented through assigning tasks, applying consequences for students who did not complete assignments, and habituating students to complete their obligations independently. In addition, teacher role modeling became an important aspect in character building through punctuality, neatness, and teachers’ daily behavior. The inhibiting factors in character development were the lack of parental supervision and the influence of technological developments on students’ learning behavior.